2021
DOI: 10.3390/antiox10121979
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral Antioxidant Supplementation at Birth Improves the Response to Intranasal Vaccination in Newborn Dairy Calves

Abstract: Newborn calves experience oxidative stress throughout the first month of their life, which is known to decrease lymphocyte functions relevant to vaccine responsiveness. Thus, this study aimed to determine the extent to which parenteral antioxidant supplementation given at birth improves the response to an intranasal viral vaccine in the first month of life of newborn dairy calves. For this, 21 calves were randomly assigned at birth to one of two commercially available antioxidant micronutrient supplements or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…This OS impairs immune function (4). Recent research has shown that antioxidant supplementation supports a more robust immune response in dairy calves (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…This OS impairs immune function (4). Recent research has shown that antioxidant supplementation supports a more robust immune response in dairy calves (5,6).…”
Section: Introductionmentioning
confidence: 99%